(untitled) (Fiep Bulletin - online, 2011)
The aim of the study was a survey of health indicators, such as habits and physical activity correlate with the level of fitness, aerobic endurance, the students of the Instituto Federal de Alagoas - IFAL. The sample used here consisted of 83 students IFAL, 42 girls and 41 boys enrolled who attend physical education classes, aged between 14 and 17 years. For data collection, we used: the questionnaire of habitual physical activity (HPAQ) test and the 12 minutes Cooper. The results showed as regards the level of physical activity which, at most, 42% of the assessed present themselves active, while 13% are rated as Very Active Moderately Active 29% and finally 16% are inactive. In relation to aerobic capacity, it was observed that the vast majority are classified as very weak level of aerobic physical activity assessed at 65%, where we also note that 19% is Poor, 10% classified as medium 5 % Good and only 1% as "Very Good" The survey results show that among the students assessed, the fact that they are usually active does not necessarily guarantee that they can be physically fit.